Ecology and biodiversity of macrofauna in a mangrove fringed lagoon, south-west coast of India - Marakala, C; Rajesh, K M; Naik, M Ganapathi; Mridula, R M (Indian Journal of Fisheries, 2011)
The study was carried out in the mangrove fringed brackishwater lagoon (15 ha) along south-west coast of India having an average depth of 1m. A long sandy beach separates the lagoon during summer, while during monsoon season the strip of sand bar breaks open into the sea. The samples were collected in triplicate from 4 stations once a month from May 1998 to April 1999. The area under study is an important nursery ground for most of the finfish and shellfish and also serves as a centre for fish seed collection owing to its rich mangrove vegetation. Water quality parameters â€“ temperature, pH, dissolved oxygen and salinity fluctuated between 27.2 and 35.1Â°C, 7.08 and 7.63, 3.2 and 6.28 ml/l and 0.36 and 26.43 ppt respectively. The nutrients such as nitrite, nitrate, phosphate and silicate ranged from 0.07 to 0.54 mg-at/l, 2.32 to 9.76 mg-at/l, 0.36 to 1.64 mg-at/l and 29.8 to 114.77 mg-at/l respectively. The higher percentage of sand was observed throughout the study period at all the stations with silt and sand fractions more or less similar in their distribution. Among macrofauna, polychaetes (39.46 to 75.97 %) were the dominant groups followed by molluscs (13.34 to 46.55 %), finfish (8.43 to 35.09 %) and crustaceans (0.95 to 3.72 %) at different stations. Seasonally, the density was higher during premonsoon followed by postmonsoon and monsoon season.